Analisis Modul Ajar Bahasa Inggri Fase D Kurikulum Merdeka pada Aplikasi Platfoam Merdeka Mengajar (PMM) - Nurlaili Nurlaili; Horia Siregar; Novita Andini (Departement of Mathematics Education, 2024)
A teaching module is a guide or guide for teachers to carry out activities in the classroom. The independent curriculum teaching module is a tool to see the achievement of student learning outcomes. However, there are still teachers who do not comply with the writing of modules according to the Ministry of Education and Culture's teaching module writing guidelines. This research aims to describe the structure of writing teaching modules in the PMM application. The research method will be carried out using a descriptive qualitative method whose data is taken from the English teaching module phase D which has implemented the independent curriculum in the PMM application. Then the data will be grouped according to theory and analyzed, then it will be adjusted to the structural writing of the Ministry of Education and Culture's independent curriculum teaching modules. In preparing teaching modules, many teachers experience difficulties in determining the learning model and writing the syntax at the core of the learning activity. After conducting analysis on the Merdeka Mengajar Platform (PMM), it can be concluded that around 70% of errors were found in determining the TP (Learning Objectives) of the 15 phase D English language teaching modules and 80% of errors were found in determining the learning model on the Merdeka Mengajar Platform (PMM).